Dosing of Antimicrobials in the Neonatal Intensive Care Unit: Does Clinical Practice Reflect Pharmacokinetics-based Recommendations?. Issue 8 (August 2020) - Stark, Ashley; Childers, Julie; England, Morgan; Clark, Reese H.; Laughon, Matthew; Cohen-Wolkowiez, Michael; Benjamin, Daniel K.; Smith, P. Brian; Wade, Kelly; Greenberg, Rachel G.
Abstract : Background: We sought to compare meropenem and fluconazole dosing in the neonatal intensive care unit with recommendations based on published pharmacokinetic (PK) studies in infants. Methods: We performed an observational cohort study of infants <90 days postnatal age who received a course of meropenem or fluconazole who were treated in neonatal intensive care units managed by the Pediatrix Medical Group (1997–2016). We defined any dose amount from 80% to 120% of the published recommendation to constitute an appropriate dose of either antimicrobial. We calculated the percentage of appropriately dosed courses overall and by discharge year. We then evaluated the change in appropriate dosing over time using a nonparametric test of trend to evaluate the proportion of appropriately dosed courses of each antimicrobial by discharge year. Results: A total of 3608 infants were administered 2025 courses of meropenem and 1201 courses of fluconazole. Of all meropenem courses, 32% were dosed appropriately (increased significantly over time; P = 0.01), while 17% of fluconazole courses were dosed appropriately (increased significantly over time; P = 0.01). Median dosing for both meropenem and fluconazole was at or below recommendations; therefore, under-dosing was more common. Conclusions: There was marked discordance between actual fluconazole and meropenem dosing and dosing recommendation in PK publications, yet adherence to PK-based doses showed improvement over time.